IMF Survey, Volume 35, Issue 05. (IMF Survey; IMF Survey ;, 2006)
IMF pandemic preparations; enlarged EU: labor, capital; Asia outlook bright; India: reforms and growth; Italy: gloomy outlook; IMF sanctions on Zimbabwe; Friedman: morals, growth; central bank communications; effective use of increased aid.